Particularities of the police tactic in security accidents - Kralj, Dražen; Solomun, Davor; Jozić, Marijan (Crisis Management Days, 2024)
The tactics of police action is a complex and very important aspect of the scope, function and security role of police organizations and services. This is a sui generis tactic that is most often inherent exclusively to the police scope, but due to the heterogeneity of assumed and real situations to which this scope refers, this tactic assumes an inter and multi disciplinary approach, both in the creation of its material meaning and even more so in the cataloguing of the implementation spectrum of procedures, measures and instruments that make up this tactic. With its elementary form and content, police tactics is placed in the field of organizational sciences and management, but due to its police meaning, this tactic also creates a new discipline that can be placed in the context of police sciences. Security events such as accidents in industrial infrastructures, due to their characteristics, especially due to the potential threat to the security situation in the immediate or distant environment, assume the urgent action of numerous and different services with the primary goal of protecting and saving people’s lives and property. However, police tactics in such events are strongly determined by a double function, which is imperative to achieve two important tactical goals. The primary goal is the rescue and protection of people and property, as well as the prevention of the spread of threats and harmful consequences, while the second is related to crime investigation and processing of events. This paper points to the immediate implementation of tactical measures and the need for coordination of police intervention with other emergency services, but also analyses the peculiarities of work at the scene for the purpose of criminal investigation of the event. At the same time, the aim of the paper is to question the specifics of the applied police tactics with the purpose of improving and more efficiently organizing police work in accidental events. Methodology In accordance with the subject of the research, and the composition and goal of this paper, respectively the peculiarities of police tactics in accidental security events, a special methodological framework of analysis was created. Since the goal of the research is an empirically based questioning of the adequacy and specificity of police tactics in accidental security events, as a basis for the description and testing of individual phases, measures, and actions, the method of case analysis (case study) was used. Through the created form, respectively the created matrix, the common and specific features of several selected, complex, typical accidental security events in which the application of police tactics is manifested were extracted as variables. Based on the analysis, all variables were synthesized, which were then interrogated through a multi-level normative framework and rules of police behaviour and profession with the ultimate goal of identifying critical points and rating the adequacy and uniqueness of the applied tactics. Results The description of the selected (5) subject cases, structured according to about 10 variables, related to and was carried out on about fifty positions in the created analysis matrix. These positions represent indicators and measurable indicators of the applied tactical measures, respectively the development and course of the intervention, but also the outcomes and achieved tactical goals. By looking at the normative framework as an element of legal admissibility and regularity, as well as the lege artis aspects and the logical justification of the tactical measures and actions it can be assessed that the police forces in the analysed cases acted in accordance with legal norms, bylaws and professional principles, and successfully achieved the expected and assumed tactical goals. Tactical measures in the function of creating assumptions for the successful operation of other emergency services (firefighters, emergency medical assistance, civil protection, etc.), especially tactical measures in traffic (control, blockade and diversion), are usually considered routine, but often they represent an obstacle and complicating the action of all services at a security event. Criminalistic differential diagnosis is inseparable and assumes simultaneous tactical measures and actions already with the first knowledge or tactical measure of action according to the information about the event. However, this diagnosis of the event usually requires numerous tactical actions related to the scene of the event, as well as actions in relation to the relevant participants, such as perpetrators, victims, witnesses, etc. The peculiarities of tactical measures in the function of criminal investigation, as well as those in the function of creating assumptions for the effective operation of other emergency services, were checked and determined in the managerial cycle segment as well. The police organization and management system are often put to the test in accidental security events, but research confirms relatively high compliance and functionality of all levels from programming and planning to monitoring the implementation of tactical measures and actions. The results also reveal that one of the most significant peculiarities of police tactics is the level of situational efficiency and competence of police officers as immediate executors of the analysed tactical measures and actions. This segment of tactics is connected to other disciplines (especially kinesiology), so it is not inspected in depth in this paper, but it is important to point out that the success of achieving tactical goals depends significantly on the psychophysical conditions and overall abilities of police officers